U-PB DATING AND GEOCHEMICAL CONSTRAINTS TO EARLY CRETACEOUS HYDROTHERMAL DOLOMITIZATION IN THE PROVENÇAL DOMAIN (MARITIME ALPS, NW ITALY - SE FRANCE) - Barale, Luca; Bertok, Carlo; d'Atri, Anna; Piana, Fabrizio; Bernasconi, Stefano; Czuppon, György; Palcsu, László; Gerdes, Axel; Birgel, Daniel; Martire, Luca (Ofioliti, 2021)
In the Maritime Alps (NW Italy - SE France), the Middle Triassic-Berriasian platform carbonates of the Provençal Domain are locally affected by an intense hydrothermal dolomitization. This dolomitization resulted from a large-scale hydrothermal circulation related to deep-rooted faults, and is indirect evidence of a significant earliest Cretaceous fault activity in this part of the Alpine Tethys European palaeomargin. New carbonate U-Pb dating and geochemical (stable isotope and noble gases on inclusion-hosted water, 87Sr/86Sr, clumped isotopes) data allowed a better understanding of the timing and mechanisms of the hydrothermal circulation. Hydrothermal fluids probably originated from seawater, which was involved in a deep circulation within the underlying crystalline basement, undergoing heating to more than 200°C and substantial compositional modification by prolonged interaction with basement rocks. Thin cement rims rich in carbonaceous material, locally alternated with hydrothermal dolomite cements, are interpreted as remnants of ephemeral microbial communities that could colonize the upper part of hydrothermal conduits during periods of reduced hot fluid flow and contemporaneous downward seawater infiltration.